Selective arterial Embolisation of Aneurysmal Bone Cysts of the Sacrum: a promising Alternative to Surgery - Henrichs, M. P.; Beck, L.; Gosheger, G.; Streitbuerger, A.; Koehler, M.; Heindel, W.; Hardes, J.; Vieth, V. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: The sacrum is a rare but unfavourable location for Aneurysmal Bone Cysts (ABCs), surgical procedures aiming to achieve local tumour control can be mutilating. Aim of this study was to evaluate whether selective arterial embolisation (AE) of ABC of the sacrum is an effective treatment and might be an alternative to surgical treatment options.Materials and Methods: Between 2007 and 2011 six patients (mean age 13.7 years, range 8 – 18 years) with an ABC of the sacrum were treated by AE. Follow-up was performed by MRI-scans as well as clinical examination (mean 36.5 months, range 14 – 56 months).Results: No treatment related complications have been observed. AE resulted in devascularisation of ABC and led to local tumour control in all patients. A partial consolidation was noticed in three patients. Pain relief was achieved in five of six patients, neurological deficits dissolved. In two patients more than one embolization was necessary. In one of these patients due to exacerbation of pain a surgical decompression was performed.Conclusion: AE of sacral ABCs can serve as an effective and safe treatment option. Thus it might be an alternative to potentially harmful surgical procedures. In case of ongoing tumour growth or pain recurrence AE can be repeated. In case of treatment failure surgical interventions are still possible.Key Points:• transarterial embolisation enables local tumour control in sacral ABCs• transarterial embolisation of sacral ABCs is a safe procedure• in case of tumour progression repetitive embolisations are possible and effectiveCitation Format:• Henrichs MP, Beck L, Gosheger G et al. Selective arterial Embolisation of Aneurysmal Bone Cysts of the Sacrum: a promising Alternative to Surgery. Fortschr Röntgenstr 2016; 188: 53 – 59
Keywords: aneurysmal bone cyst; selective arterial embolization; sacrum; bone tumor